2019
DOI: 10.1136/tobaccocontrol-2019-054949
|View full text |Cite
|
Sign up to set email alerts
|

Heated tobacco product use among Korean adolescents

Abstract: BackgroundHeated tobacco products (HTPs) may compromise decades-long efforts to marginalise the tobacco industry. Their appeal to adolescents imposes a risk of a new tobacco epidemic. Empirical evidence on the behavioural patterns of HTP use among adolescents is required. We investigated the prevalence of HTP use and the association between use of HTPs and e-cigarettes and attempts to quit smoking cigarettes.MethodsNationally representative cross-sectional survey data of South Korean adolescents aged 12–18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 15 publications
5
35
2
Order By: Relevance
“…ENDS are sometimes considered to reduce the harm of tobacco use 30 ; but this is disputed by our findings on the actual behavior of adolescents. We found that the risk of initiating cigarette use increases markedly after experimentation with ENDS, and a previous study reported that the majority of adolescent ENDS users were also cigarette users 31 . The results of our study showed the prevalence of current cigarette smoking was 1.2fold higher for those who started cigarette smoking subsequent to ENDS use, compared to those who had not experimented with ENDS.…”
Section: Discussionsupporting
confidence: 57%
“…ENDS are sometimes considered to reduce the harm of tobacco use 30 ; but this is disputed by our findings on the actual behavior of adolescents. We found that the risk of initiating cigarette use increases markedly after experimentation with ENDS, and a previous study reported that the majority of adolescent ENDS users were also cigarette users 31 . The results of our study showed the prevalence of current cigarette smoking was 1.2fold higher for those who started cigarette smoking subsequent to ENDS use, compared to those who had not experimented with ENDS.…”
Section: Discussionsupporting
confidence: 57%
“…reported having used IQOS (referred to in this study as "ever HTP use") and 3.5% were current users. 29) Kang and Cho 30) reported that 2.8% of adolescents in the KYRBS 2018 studies were ever HTP users.…”
Section: Prevalence Of Heated Tobacco Product Usementioning
confidence: 99%
“…Among 228 young adults aged 19–24 years old, 5.7% reported having used IQOS (referred to in this study as “ever HTP use”) and 3.5% were current users [ 29 ]. Kang and Cho [ 30 ] reported that 2.8% of adolescents in the KYRBS 2018 studies were ever HTP users. Compared with e-cigarettes, this data representative of the South Korean population showed a much faster expansion of HTP use.…”
Section: Trends In Tobacco Use In South Koreamentioning
confidence: 99%
“…That is much lower than the general tobacco use rate (21.56%) but strongly suggests that 96.25% of HTP users are or were dual users 2 . It is also noteworthy that the rate of use amongst adolescents reached 2.8% one year after their introduction 3 . As of April 2019, sales of HTPs reached approximately 11.8% of total tobacco sales in Korea 4 .…”
Section: Introductionmentioning
confidence: 98%